1997
DOI: 10.1084/jem.185.8.1447
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis of Staphylococcal Superantigen Toxins

Abstract: Staphylococcus aureus produces a set of proteins (e.g., staphylococcal enterotoxin A [SEA], SEB, toxic shock syndrome toxin 1 [TSST-1]) which act both as superantigens (SAgs) and toxins. Although their mode of action as SAgs is well understood, little is known about how they enter the body via the intestine and cause food poisoning. To examine this problem we used an in vitro culture system to study the capacity of class II MHC-negative human intestinal epithelial cells (Caco-2) to transcytose several staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
93
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 46 publications
(41 reference statements)
4
93
2
Order By: Relevance
“…However, we also investigated the effect of SEB pretreatment in our model of oral tolerance and airway allergy and found that SEB was less effective and less reliable in improving oral tolerance compared with SEA (unpublished data). The greater efficiency of SEA might be due to the fact that SEA can reside in the gut, whereas SEB is more readily transcytosed over the gut epithelium and enters the blood stream [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also investigated the effect of SEB pretreatment in our model of oral tolerance and airway allergy and found that SEB was less effective and less reliable in improving oral tolerance compared with SEA (unpublished data). The greater efficiency of SEA might be due to the fact that SEA can reside in the gut, whereas SEB is more readily transcytosed over the gut epithelium and enters the blood stream [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, we also investigated the effect of SEB pretreatment in our model of oral tolerance and airway allergy and found that SEB was less effective and less reliable in improving oral tolerance compared with SEA (unpublished data). The greater efficiency of SEA might be due to the fact that SEA can reside in the gut, whereas SEB is more readily transcytosed over the gut epithelium and enters the blood stream [33].Extensive variability between individual mice in the response to antigen challenge characterised the orally tolerised sham pretreated mice, wheras SEA pre-treated mice were remarkably tolerant with a minimal spread among individual animals. It seems as though SEA pre-treatment maximises the capacity to develop tolerance after feeding, whereas the process is more variable in efficiency in control mice, probably due to individual differences regarding conditions prevailing in the gut at the time point for tolerisation.…”
mentioning
confidence: 99%
“…Moreover, multiple lines of evidence have accumulated to suggest that staphylococcal enterotoxins can cross the epithelial barrier in an immunologically intact form through transcytosis (33,34). Thus, the probability that staphylococcal enterotoxin can directly interact with the second layer of nonprofessional immunological defense, e.g., IMFs, is high.…”
Section: Discussionmentioning
confidence: 99%
“…IMFs form an interface between the epithelium and lamina propria immune cells and have been implicated in the regulation of mucosal inflammation (31,32). Thus, given the unique subepithelial location of MHC class II ϩ IMFs with respect to mucosal lymphocytes, as well as the fact that staphylococcal enterotoxins can cross the intestinal epithelial barrier in immunologically active form (33,34) and increase epithelial permeability (35)(36)(37), it is important to study the role of IMFs in the initiation of the staphylococcal enterotoxin-associated immunopathogenesis.…”
mentioning
confidence: 99%
“…Recently, SEB has been shown to cross the intestinal epithelial cell barrier (38) and stimulate T cells (39 -41), leading to the activation of T cells producing IFN-␥ and IL-2 (42). Based on the results presented in this report, any stimulation that activates a relatively large subset of T cells generates autoreactive T cells that proliferate when re-exposed to self Ags expressing class II MHC.…”
Section: Discussionmentioning
confidence: 99%